2020
DOI: 10.1016/j.lfs.2019.117090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms by which SGLT2 inhibitors can induce insulin sensitivity in diabetic milieu: A mechanistic review

Abstract: Sodium-glucose co-transporter-2 inhibitors (SGLT2i) are a relatively newer class of antihyperglycemic medications that reduce blood glucose by inhibition of renal glucose re-uptake, thereby increasing urinary glucose excretion. Although glycosuria is the primary mechanism of action of these agents, there is some evidence suggesting they can reduce insulin resistance and induce peripheral insulin sensitivity. Identifying the molecular mechanisms by which these medications improve glucose homeostasis can help us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 102 publications
(175 reference statements)
1
60
0
1
Order By: Relevance
“… 82 In addition to their glucose-lowering effect, they can also improve insulin sensitivity via several molecular pathways including reduction of glucotoxicity and lipotoxicity, enhance β-cells function, reduce the oxidative damage and inflammatory processes, improve caloric deposition and weight loss. 83 …”
Section: Treatment Options For Managing Metabolic Comorbiditiesmentioning
confidence: 99%
“… 82 In addition to their glucose-lowering effect, they can also improve insulin sensitivity via several molecular pathways including reduction of glucotoxicity and lipotoxicity, enhance β-cells function, reduce the oxidative damage and inflammatory processes, improve caloric deposition and weight loss. 83 …”
Section: Treatment Options For Managing Metabolic Comorbiditiesmentioning
confidence: 99%
“…SGLT 2 inhibitors, such as dapagliflozin and empagliflozin, decrease renal glucose reabsorption, resulting in enhanced urinary glucose excretion and subsequent reductions in plasma glucose and glycosylated hemoglobin concentrations( Nauck, 2014 ). SGLT2 inhibitors could improve insulin sensitivity and glucose homeostasis via reducing glucotoxicity, improving β cell function, reducing oxidative damages and inflammatory processes and inducing caloric disposition and weight loss( Yaribeygi et al, 2020 ). Dapagliflozin could improve brain insulin sensitivity, alleviate brain mitochondrial dysfunction, attenuate brain apoptosis and brain inflammation, and preserve hippocampal synaptic plasticity( Sa-nguanmoo et al, 2017 ).…”
Section: Repurposing Of Anti-diabetic Agents As a Potential Treatmentmentioning
confidence: 99%
“…is process does not depend on insulin resistance and β-cell function [20]. Recent studies have shown that in addition to lowering blood glucose, the SGLT2 inhibitor dapagliflozin…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors, which act independently of insulin, selectively inhibit SGLT2 in the kidney and block the reabsorption of glucose, thereby lowering blood glucose levels. This process does not depend on insulin resistance and β -cell function [ 20 ]. Recent studies have shown that in addition to lowering blood glucose, the SGLT2 inhibitor dapagliflozin also has a positive effect on patients with heart failure [ 10 12 , 21 23 ].…”
Section: Discussionmentioning
confidence: 99%